'METALLOTHIONEIN': SUATU PARAMETER KUNCI YANG PENTING DALAM PENETAPAN BAKU MUTU AIR LAUT (BMAL) INDONESIA - Markus T. Lasut (EKOTON, 2012)
The sensitive, accurate and valid methods for metal contamination are important to control and monitor metal pollution which is dangerous to marine ecosystem, alter sustainable living environment, and human being. This is based on facts that dangerous wastewater substances (in Indonesia is called B3) is increase as industrialization in all sectors increases, the B3 wastes are discharged to marine environment, and, however, it is still categorize as ‘environmentally save’ wastes based on Indonesian Wastewater Quality Standard (IWQS).The phenomenon of metals concentrated into the tissues of marine organisms was found related to the role of metal-binding proteins. The function of proteins is to bind many metal ions, these proteins are named as metallothioneins. The proteins are a group of specific non-enzyme proteins that are increasingly being demonstrated to play a central role in metal metabolism.IWQS is not a inflexible requirement, but it could be revised and developed based on some circumstances and recent technology. It is a matter a fact that determination of IWQS is addressed not only for ecosystem protection but also protection to entire living environment and human being as an actor in environmental conservation. Therefore, sensitive, accurate and valid methods for measuring pollution levels are needed as an alternative to complete the IWQS. So, metallothionein as discussed above, could be as one of the method. In addition, the method can also be applied to determine the dangerous and poisonous substances (B3), completing the toxicity tests and other method in IWQS.